Analisis Stabilitas Lereng Timbunan dengan Perkuatan Geosintetik. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Kehutanan UGM, 1999)
ABSTRACT Problem of soft soils is very complicated, due to their physical and mechanical characteristics. Method and analysis of the soil treatment by physical, mechanical, and chemical means have already been used. t: One of the soil treatment is soil reinforcement using mechanical method which has been developed recently. The method in analyzing soil reinforcement employs combination of the limit-equilibrium-method and the reinforcement' function. Key word: Geosintetik, stabilitas lereng, kelongsoran lereng